Human Iris Image Recognition System for Biometrics Application - Lee, Peik Shyan (2004)
Biometrics is the recent technology that designed to solve the problem caused by individual identification. In this thesis, an iris image recognition system for biometrics applications is presented. The iris recognition system consisted of four major steps: biological data acquisition, image processing, feature extraction and pattern matching.